2014
DOI: 10.1371/journal.pone.0108178
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Placebo-Controlled Study on the Effects of Lutein and Zeaxanthin on Neural Processing Speed and Efficiency

Abstract: Lutein and zeaxanthin are major carotenoids in the eye but are also found in post-receptoral visual pathways. It has been hypothesized that these pigments influence the processing of visual signals within and post-retina, and that increasing lutein and zeaxanthin levels within the visual system will lead to increased visual processing speeds. To test this, we measured macular pigment density (as a biomarker of lutein and zeaxanthin levels in brain), critical flicker fusion (CFF) thresholds, and visual motor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 41 publications
2
93
0
Order By: Relevance
“…Another possibility, more relevant to younger individuals and palliative approaches, is a direct improvement by some type of local interaction with neural cells (the so-called neural efficiency hypothesis; [11,36,21] MPOD) in young healthy subjects would yield behavioral improvements in tasks that are generally mediated by the central nervous system. 2 To test this idea, we measured MPOD and temporal vision (specifically, the temporal contrast sensitivity function, tCSF) in a group of young healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility, more relevant to younger individuals and palliative approaches, is a direct improvement by some type of local interaction with neural cells (the so-called neural efficiency hypothesis; [11,36,21] MPOD) in young healthy subjects would yield behavioral improvements in tasks that are generally mediated by the central nervous system. 2 To test this idea, we measured MPOD and temporal vision (specifically, the temporal contrast sensitivity function, tCSF) in a group of young healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Significant relations have been reported between macular pigment optical density (MPOD; L and Z and meso-Z measured in the retina) and a large number of visual measures including glare disability and discomfort, photostress recovery, and chromatic contrast [13]. Measures of L and Z within the retina appear to be strongly linked to measures of L and Z in brain tissue [29] and MPOD has also been linked to measures that are mediated by brain such as cognition [15,9,23], auditory thresholds [33], balance time, reaction time [22], and temporal vision [11,21,2].Taken together, L and Z seem important to biology, in general, and humans are no exception. In many cases, the basis for their functional effects has been well characterized.…”
mentioning
confidence: 99%
“…Bovier et al found moderate but statistically signiicant improvements in both MPOD and cognitive function with lutein and zeaxanthin supplementation of young, healthy individuals considered to be at peak cognitive eiciency [34]. These studies suggest that both young, healthy adults and the elderly population can gain cognitive beneits from lutein and zeaxanthin supplementation.…”
Section: Neural Processingmentioning
confidence: 95%
“…Additionally, MPOD correlates with processing speed and cognitive performance in healthy elderly subjects as well as those with mild cognitive impairment [4749]. Another study found moderate but statistically significant improvements in both MPOD and visual processing speed when supplementing young and healthy individuals considered to be at peak cognitive efficiency [50]. …”
Section: Macular Pigment and Visual Performancementioning
confidence: 99%